Effects of flour quality and drying rates controlled by temperature, air circulation, and relative humidity on the quality of dried white‐salted noodles. Issue 6 (5th September 2019) - Moon, Yujin; Kim, Kyeong Hoon; Kweon, Meera
Abstract: Background and objectives: The production and consumption of dried white‐salted noodles in Korea are higher than that of fresh white‐salted noodles. Flour quality and appropriate drying conditions are essential to produce high‐quality dried noodles. This study aimed to scientifically explore the impact of flour quality and the drying rate, which was controlled by varying the temperature and relative humidity and applying air circulation, on the quality of dried white‐salted noodles. Findings: Increasing the drying rate by increasing the temperature or applying air circulation/ventilation caused more severe cracks in all the dried white‐salted noodles made from three flours with different ash contents. The noodles dried at 30°C without applying air circulation and those dried using a stepwise drying procedure with controlled relative humidity showed no cracks and remained intact after cooking. Conclusions: Drying rate was more critical than flour quality to produce noodles with desirable attributes. The application of air circulation is not recommended, even at 30°C, as micro‐cracks form due to internal stress. Significance and novelty: The negative effect of accelerated drying using increased temperature and circulating air on the quality of dried and cooked white‐salted noodles was reported scientifically for the first time.